Correlation between different levels of Her-2 protein expression and the efficacy of neoadjuvant therapy in Her-2 positive breast cancer - Wang, Wen-hui; Li, Hong-bo; Cui, Zhong-yuan; Li, Yan-dong; Wang, Zhi-yong (Frontiers in Oncology, 2025)
IntroductionThe purpose of this study was to explore the correlation between the difference of Her-2 protein expression level in Her-2 positive breast cancer and the efficacy of neoadjuvant chemotherapy, so as to determine the best population for neoadjuvant treatment of Her-2 positive breast cancer.MethodsThis study enrolled 161 Her-2 positive breast cancer patients who received trastuzumab plus pertuzumab therapy between January 2020 and January 2024. Statistical analyses were employed to evaluate associations between Her-2 protein expression levels and clinicopathological characteristics, as well as relationships between pathological complete response (pCR) and these features. Logistic regression was used to assess correlations between Her-2 expression levels and clinicopathological factors, and to analyze pCR predictors.ResultAmong the 161 patients receiving neoadjuvant trastuzumab-pertuzumab therapy, 81 achieved pCR (50.31%), while 80 did not (49.69%). In the Her-2 (3+) subgroup (n=134), 58.21% (78/134) attained pCR versus 41.79% (56/134) with non-pCR. For Her-2 (2+)/FISH(+) patients (n=27), only 11.11% (3/27) achieved pCR, contrasting with 88.89% (24/27) showing non-pCR. Univariate analysis identified hormone receptor status, tumor size, and Her-2 expression level as pCR influencers. However, multivariate logistic regression confirmed Her-2 expression as the sole independent predictor: Her-2 (3+) patients had significantly higher pCR rates than Her-2 (2+)/FISH(+) cases (p=0.005; OR: 0.170 [95% CI: 0.045–0.639]).ConclusionHer-2 (3+) expression correlates with superior pCR rates, underscoring the need for further research to refine patient selection for optimized targeted therapy benefits.